Understanding the propensity to undergo genetic testing in patients affected by inherited retinal diseases: a twelve-item questionnaire. (2nd January 2023) - Bottazzi, Leonardo; Antropoli, Alessio; Bianco, Lorenzo; Andrao, Assia; Galimberti, Gabriele; Mascetti, Sergio; Arrigo, Alessandro; Saladino, Andrea; Bandello, Francesco; Parodi, Maurizio Battaglia
ABSTRACT: Background: The diagnosis of inherited retinal diseases (IRDs) can only be confirmed through genetic testing. The aim of our study is to investigate the propensity of Italian patients affected by IRDs to undergo genetic testing. Materials and methods: One hundred and thirty-two patients diagnosed with IRDs referred to Italian Retina Onlus were enrolled from 1 st January 2021 to 31 th December 2021 in this cross-sectional study to answer to a twelve-item questionnaire. Results: One hundred and four patients were aware of the possibility of taking a genetic test, and 94 of them did. Most of genetically tested patients (93.6%) had been informed about advantages and limitations of genetic investigations. The most common reason for undergoing genetic testing was to gather information for their relatives, while the most frequent reason for patients not taking the test was lack of someone who encourages them to do so. Most of genetically tested patients believed that the results could aid medical research in the search for a treatment for IRDs, while who did not undergo DNA testing often did not have a clear opinion on the topic. Almost all patients (98.9%) performed the test through the Italian National Health System. Conclusions: Our study investigated the tendency of Italian patients affected by IRDs to undergo genetic testing, highlighting the importance of educating both patients and healthcare professionals on this topic.